What Factors Drive Job Seekers Attitude in Using E-Recruitment? - Brahmana, Ritzky Karina; Brahmana, Rayenda (UI Scholars Hub, 2013)
In a digital world, job seekers prefer to use e-recruitment for a vacancy searching. Thus, the explanation of the determinants of their attitude in using this technology is left unobserved. This article reports the result of a survey study on how users utilize e-recruitment to search for works. Three hundred eighty-five just-graduated undergraduate students answered questions regarding their intention of using the e-recruitment under Theory of Acceptance Model. We propose Perceived Usefulness, Perceived Ease of Use, and Perceived of Enjoyment as the determinants of the job seekers intention. Results showed that those three variables influence the decision making of job seekers. We found also Perceived Usefulness is the mediating effect for jobs seekers in easy-to-use and enjoy feeling. This article provides evidence that e-recruitment has to be friendly user and fun to use to attract job seekers intention.